2020
DOI: 10.1016/j.biochi.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Bis(monoacylglycero)phosphate, an important actor in the host endocytic machinery hijacked by SARS-CoV-2 and related viruses

Abstract: Viruses, including the novel coronavirus SARS-CoV-2, redirect infected cell metabolism to their own purposes. After binding to its receptor angiotensin-converting enzyme 2 (ACE2) on the cell surface, the SARS-CoV-2 is taken up by receptor-mediated endocytosis ending in the acidic endolysosomal compartment. The virus hijacks the endosomal machinery leading to fusion of viral and endosomal membranes and release of the viral RNA into the cytosol. This mini-review specifically highlights the membrane lipid organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 127 publications
0
15
0
Order By: Relevance
“…Upon binding, the host protease, transmembrane protease serine 2 (TMPRSS2), expressed on the cell membrane, cleaves S into the S1 and S2 subunits to activate S to facilitate virus‐host cell fusion 48 . In the endosomal pathway, SARS‐CoV‐2 also binds ACE2, but instead of activating TMPRSS2, SARS‐CoV‐2 is internalized via clathrin‐mediated endocytosis 49 . Thus, in both pathways, ACE2 plays an essential role to induce viral cell invasion.…”
Section: Obesity and Related Metabolic Disturbances Increase The Risk Of Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…Upon binding, the host protease, transmembrane protease serine 2 (TMPRSS2), expressed on the cell membrane, cleaves S into the S1 and S2 subunits to activate S to facilitate virus‐host cell fusion 48 . In the endosomal pathway, SARS‐CoV‐2 also binds ACE2, but instead of activating TMPRSS2, SARS‐CoV‐2 is internalized via clathrin‐mediated endocytosis 49 . Thus, in both pathways, ACE2 plays an essential role to induce viral cell invasion.…”
Section: Obesity and Related Metabolic Disturbances Increase The Risk Of Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…BMP prevents the formation of 7KC in murine macrophagic RAW264.7 cells [ 101 ]. Recently, it has been suggested that BMP could be useful in the prevention of SARS-CoV-2 infection [ 102 ]. It is hypothesised that BMP, which is present in the endosomes and is involved in the intracellular cholesterol trafficking, could act on the SARS-CoV-2 viral cycle and reduce virus production.…”
Section: -Ketocholesterol-modifying Drugs In Covid-19mentioning
confidence: 99%
“…It has been furthermore suggested that the unique anionic lysosomal lipid BMP plays an important role in viral infections [194] and that the secretory ASM is required for the virus entry at the plasma membranes [190], reducing their high SM levels and leading to an internalization of the virus [195]. It has also been shown that sphingosine could be exploited as an antiviral compound.…”
Section: The Role Of Asm In Bacterial Mycobacterial Fungal and Viral Infectionsmentioning
confidence: 99%